Development of MSMEs in the Garment Industry through Online Media - Rahmania, Nurani; Fauzi, Muhamad Umar; Prasnowo, M Adhi; Handayani, Wiwik; Pujowati, Yenik (Bisma : Bimbingan Swadaya Masyarakat, 2023)
This assistance aims to develop the economic sector of MSMEs in Kutorejo Kec. Kertosono village of nganjuk regency through the KPM-IK STAI Miftahul'ula Kertosono Nganjuk program. The methods in this study use the Asset Based Community Developmet (ABCD) approach or asset-based community empowerment approach. Through this Asset Based Community Development (ABCD) approach can continuously form community independence in increasing income so as to improve their well-being. The development of MSMEs is carried out through the Online Market and is proven to have a positive impact with the increasing turnover of income from MSMEs "Convection Yoris".